Ethnomatematics In Mathematics Learning on The Perspective of Perenialism Philosophy - Febria Dewi Pratiwi (Universitas Sebelas Maret, 2019)
Ethnomatematics in mathematics has the meaning as a new study that has the potential to be developed into the latest learning innovations containing a combination of contextual learning and at the same time introducing culture in Indonesia to learners. So that ethnomatematika can be used as a method of teaching and learning process in the field of mathematics. The view of mathematics learning as rationality and the principle of freedom which means freedom to learn to other objects without being bound by the provisions that are tightened through the culture around the environment. The research method used is the library research method. Information that has been collected and analyzed is secondary information in the form of research results including books, articles, and journals that correspond to the topic to be discussed. The authors examined some of the ideas, opinions, or findings contained in the literature, so that this study will provide theoretical information related to ethnomatematics in the study of mathematics on the perspective of perenialism. After being analyzed, the results of the analysis were associated and adapted to the ethnomatmatic context in mathematics learning in Junior High School (SMP) about the perspective of immortalism. So that the creation of students is free in expressing their observations in a happy and comfortable way. Although the main thing to note in perennials is students, teachers also have a role to play in the learning journey, but only as facilitators.